Human rights : a reference handbook - Whalen, Lucille (Santa Barbara, Calif. : ABC-CLIO, 1989)
A handbook listing books, periodicals, directories, non-print materi als, and other information sources on human rights, intended for resear chers, students, and activists.
Includes bibliographical references (p. 59-102).
Keywords: Human rights; Human rights -- Bibliography; Human rights -- Bibliography